Biopolymeric bilayer films produced by co-extrusion film blowing. (February 2018) - Scaffaro, Roberto; Sutera, Fiorenza; Botta, Luigi
Abstract: Biodegradable packaging promises a more environmentally friendly future. Nevertheless, a single biopolymer often lacks of some important properties. In order to contribute to this challenge, biodegradable bilayer films from poly(lactic acid) (PLA) and MaterBi ® were prepared in this work and compared with monolayer films obtained with both the polymers. The prepared films were fully characterized through morphological, mechanical, thermal, chemical, optical and water contact angle analyses. Furthermore, the hydrolytic degradation of monolayer and bilayer films was studied by performing tests at three different pH. The morphological analysis revealed that PLA/MaterBi bilayer films show good interfacial adhesion, even under the stretching in the mechanical tests. The bilayer film showed a higher stiffness than that of MaterBi and a larger elongation at break in comparison with PLA. The degradation tests revealed that weight loss is faster at pH 10 for all the systems and that at this pH the bilayer film show the highest degradation rate. Highlights: PLA/MaterBi bilayer films were successfully produced by co-extrusion film blowing. Bilayer films were compared with the respective monolayer films. Strong interfacial adhesion was obtained by adequately setting process parameters. Bilayer films show optical, thermal and mechanical properties intermediate to those of the starting polymers. In alkaline conditions bilayer films degraded faster than the respective monolayers.